THE IMPACT OF THE EDUCATION ESTABLISHMENT LEADER MANAGEMENT STYLE ON THE REACHING GOALS OF THE EDUCATION INSTITUTION - Skaistkalne-Virka, Irita; Prudnikova, Ilga (Education Reform: Education Content Research and Implementation Problems, 2021)
The purpose of the research is to investigate the management style of education establishment and its role in attaining education goals. Both theoretical and empirical research methods were used in this study. The study is based on research activities. During the study, questionnaire and test methods were applied. Questionnaire “The required knowledge, skills and personal qualities for the head of the education establishment” (Skaistkalne-Virka, 2004) in this study shows what kind of knowledge, skills and personal qualities are needed for the head of the educational establishment to possess in order to achieve the goals. Test “The head of education establishment, orientation to task or relationship with people” (Pfeiffer & Jones, 1974) as an instrument has been used to explain the head of education establishment, orientation to task or relationship with people. The test revealed the type of orientation for each of educational establishment. In conclusion: that head of educational establishment, who is orientated towards the relationship with people, has democratic management style, but who is task-orientated possesses authoritative management style.